Database Management Systems. - ESL, ITL. (2012)
Database Management Systems is designed as quick reference guide for important undergraduate computer courses. The organized and accessible format of this book allows students to learn the important concepts in an easy-to-understand, question-and-answer format. These portable learning tools have been designed as one-stop references for students to understand and master the subjects by themselves.
Variation of the hash join technique -- Multiple-choice Questions -- Answers -- Chapter 9: Introduction to Transaction Processing -- Multiple-choice Questions -- Answers -- Chapter 10: Concurrency Control Techniques -- Multiversion timestamp ordering -- Multiversion two-phase locking -- Multiple-choice Questions -- Answers -- Chapter 11: Database Recovery System -- Recovery techniques based on deferred update -- Recovery techniques based on immediate update -- Multiple-choice Questions -- Answers -- Chapter 12: Database Security -- Accidental threats -- Malicious or intentional threats -- Managing user accounts -- Database audit -- Multiple-choice Questions -- Answers -- Chapter 13: Database System Architecture -- Single lock manager -- Distributed lock manager -- Primary copy -- Majority locking -- Wait-for graph -- Time-out based technique -- Two-phase commit (2PC) -- Multiple-choice Questions -- Answers -- Chapter 14: Data Warehousing, OLAP, and Data Mining -- Multiple-choice Questions -- Answers -- Chapter 15: Information Retrieval -- Limitations of the vector space model -- Multiple-choice Questions -- Answers -- Chapter 16: Miscellaneous Questions -- Features of PostgreSQL -- Features of Oracle -- Features of Microsoft SQL server -- Features of IBM DB2 -- Object definition language -- Object query language -- Multiple-choice Questions -- Answers -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books